Multiscale modeling of blood flow: Coupling finite elements with smoothed dissipative particle dynamics - Moreno, N.; Vignal, P.; Li, J.; Calo, Victor (2013)
A variational multi scale approach to model blood flow through arteries is proposed. A finite element discretization to represent the coarse scales (macro size), is coupled to smoothed dissipative particle dynamics that captures the fine scale features (micro scale). Blood is assumed to be incompressible, and flow is described through the Navier Stokes equation. The proposed coupling is tested with two benchmark problems, in fully coupled systems. Further refinements of the model can be incorporated in order to explicitly include blood constituents and non-Newtonian behavior. The suggested algorithm can be used with any particle-based method able to solve the Navier-Stokes equation. © 2013 The Authors. Published by Elsevier B.V.